Characterization of Hemerocallis citrina Transcriptome and Development of EST-SSR Markers for Evaluation of Genetic Diversity and Population Structure of Hemerocallis Collection - Li, Sen; Ji, Fangfang; Hou, Feifan; Cui, Huliang; Shi, Qingqing; Xing, Guoming; Weng, Yiqun; Kang, Xiuping (Frontiers in Plant Science, 2020)
Hemerocallis spp. commonly known as daylilies and night lilies, are among the most popular ornamental crops worldwide. In Eastern Asia, H. citrina is also widely cultivated as both a vegetable crop and for medicinal use. However, limited genetic and genomic resources are available in Hemerocallis. Knowledge on the genetic diversity and population structure of this species-rich genus is very limited. In this study, we reported transcriptome sequencing of H. citrina cv. ‘Datonghuanghua’ which is a popular, high-yielding variety in China. We mined the transcriptome data, identified and characterized the microsatellite or simple sequence repeat (SSR) sequences in the expressed genome. From ∼14.15 Gbp clean reads, we assembled 92,107 unigenes, of which 41,796 were annotated for possible functions. From 41,796 unigenes, we identified and characterized 3,430 SSRs with varying motifs. Forty-three SSRs were used to fingerprint 155 Hemerocallis accessions. Clustering and population structure analyses with the genotypic data among the 155 accessions reveal broader genetic variation of daylilies than the night lily accessions which form a subgroup in the phylogenetic tree. The night lily group included accessions from H. citrina, H. lilioasphodelus, and H. minor, the majority of which bloom in the evening/night, whereas the ∼100 daylily accessions bloomed in the early morning suggesting flowering time may be a major force in the selection of night lily. The utility of these SSRs was further exemplified in association analysis of blooming time among these accessions. Twelve SSRs were found to have significant associations with this horticulturally important trait.